Type 7 Adenylyl Cyclase is Involved in the Ethanol and CRF Sensitivity of GABAergic Synapses in Mouse Central Amygdala - Cruz, Maureen T.; Bajo, Michael B.; Maragnoli, Elisabetta M.; Tabakoff, Boris; Siggins, George R.; Roberto, Marisa (Frontiers in Neuroscience, 2011)
Abstract The GABAergic system in the central amygdala (CeA) plays a major role in ethanol dependence and in the anxiogenic response to ethanol withdrawal. Previously, we found that both ethanol and corticotropin releasing factor (CRF) increase GABAergic transmission in mouse and rat CeA neurons, in part by enhancing the release of GABA via activation of presynaptic CRF1 receptors. CRF1 receptors are coupled to the enzyme adenylyl cyclase (AC), which produces the second messenger cyclic AMP. There are nine isoforms of AC, but we recently found that CRF1 receptors in the pituitary were coupled to the Type 7 AC (AC7). Therefore, using an in vitro electrophysiological approach in brain slices, here we have investigated a possible role of the AC7 signaling pathway in ethanol and CRF effects on CeA GABAergic synapses of genetically modified mice with diminished brain Adcy7 activity (HET) compared to their littermate male wild type (WT) mice. We found no significant differences in basal membrane properties, mean baseline amplitude of evoked GABAA receptor-mediated inhibitory postsynaptic potentials (IPSPs), or paired-pulse facilitation (PPF) of GABAA-IPSPs between HET and WT mice. In CeA neurons of WT mice, ethanol superfusion significantly augmented (by 39%) GABAA-IPSPs and decreased PPF (by 25%), suggesting increased presynaptic GABA release. However, these effects were absent in HET mice. CRF superfusion also significantly augmented IPSPs (by 38%) and decreased PPF (by 23%) in WT CeA neurons, and still elicited a significant but smaller (by 13%) increase of IPSP amplitude, but no effect on PPF, in HET mice. These electrophysiological data suggest that AC7 plays an important role in ethanol and CRF modulation of presynaptic GABA release in CeA and thus may underlie ethanol-related behaviors such as anxiety and dependence.